Research and development of a pilot continuous annealing and MgO coating line for grain-oriented silicon steel. (14th September 2022) - Hua, Fuan; Li, Jianping; Zhang, Wenkang; Zhang, Zerui; Hou, Pengfei; Niu, Wenyong
ABSTRACT: To investigate the processes of continuous annealing and MgO coating of grain-oriented silicon steel (GO), a pilot-scale line was developed, which could realize functions such as cleaning, heating, decarburization, reduction, nitriding, and MgO coating in a coil-to-coil manner. A significant feature of the pilot line is the integrated furnace consisting of six furnace units and the in-between separating devices, which work collaboratively to adjust the lengths, and to separate the annealing atmospheres and temperatures of the different process sections. A series of test runs and experiments was carried out on the line. The results showed that the pilot line had the characteristics of flexible process, accurate process parameters control and reliable atmosphere separation. The results of decarburization, reduction, nitriding, and coating met the requirements of GO. The pilot line provided an excellent platform for the experimental study of the processes of continuous annealing and MgO coating of GO.